AWARENESS CAMPAIGN ON THE IMPORTANCE OF MAINTAINING VILLAGE FACILITIES IN GAMPONG JEULINGKE, BANDA ACEH, AFTER THE ACEH NATURAL DISASTER AND TSUNAMI: PENYULUHAN PENTINGNYA MENJAGA FASILITAS DESA GAMPONG JEULINGKE BANDA ACEH SETELAH BENCANA ALAM DAN TSUNAMI ACEH - Dela Andriani; Armelia Dafrina; Muthmainnah (PT. ROCE WISDOM ACEH, 2026)
Gampong Jeulingke is one of the areas in Syiah Kuala District, Banda Aceh City, that suffered destruction as a result of the 2004 Aceh earthquake and tsunami. Through rehabilitation and reconstruction programs implemented by the Aceh–Nias Rehabilitation and Reconstruction Agency (BRR) in collaboration with the government and various international organisations, public facilities and basic infrastructure were successfully rebuilt. However, a decade after the disaster, the challenges faced by the community are no longer related to infrastructure provision but rather to low public awareness of the maintenance of existing public facilities. This community service activity aims to increase public understanding of the importance of maintaining village facilities as part of efforts to achieve sustainable development, a high-quality built environment, and to support the vision of Banda Aceh as a “Madani City.” The methods employed included outreach, participatory training, interactive discussions, and assessments of community understanding. The results of the activity demonstrated an increase in community awareness regarding the importance of maintaining public facilities, as evidenced by residents’ commitment to keeping the environment clean, a heightened sense of ownership toward village assets, and a desire to carry out maintenance activities on an ongoing basis. This initiative demonstrates that community education is a crucial strategy for ensuring the sustainability of post-disaster reconstruction outcomes.